Pious Brief Narrative in Medieval Castilian & Galician Verse : From Berceo to Alfonso X. - Keller, John Esten (Studies in Romance languages (Lexington, Ky.), 1978)
""Brief narratives, "" or medieval precursors to the modern short story, are compositions couched in the form of a tale of reasonable short length. They began with writings in Latin and, eventually, made their way into the vernacular languages of Europe. They include the fable, the apologue, the exemplum, the saint's life, the miracle, the biography, the adventure tale, the romance, the jest, and the anecdote, among others. In Spain, the oldest extant brief narratives in written form are in verse and date from the late twelfth and early thirteenth centuries. The earliest examples include La vi.